EDUKASI DENGAN MEDIA VISUAL DAN AUDIO VISUAL TERHADAP TINGKAT PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK SEKOLAH DASAR (SYSTEMATIC REVIEW) - Herlinawati Daulay; Loyd Vander Pakpahan (Poltekkes Kemenkes Medan, 2023)
Dissemination is one of the efforts that can be done to increase knowledge about dental and oral health maintenance. The use of dissemination aids is something that needs to be considered, such as the use of visual and audio visual media. This type of dissemination can be applied to various targets, but is more focused on groups of elementary school children. This study is a systematic review conducted by reviewing 10 articles published from 2018-2020, and aims to obtain a comparison between using visual and audio-visual as media for dissemination on dental and oral health maintenance on the level of knowledge of elementary school children. Through the research, the following results were obtained: the level of knowledge of children before and after dissemination using visual media about dental and oral health increased, from fair criteria (80%) to good criteria (90%); while the level of knowledge of children before and after dissemination using audio-visual media about dental and oral health increased from fair criteria (90%) to good criteria (90%). This study concludes that there are differences between dissemination using visual and audio-visual as media. Dissemination using audio-visual as media was more effective than using visual as media for dissemination (p = 0.000): (p < 0.005).